Cyclotron production of Gallium-68 Radiopharmaceuticals using the 68Zn(p,n)68Ga reaction and their regulatory aspects - Ashhar, Zarif; Ahmad Fadzil, Muhammad Fakhrurazi; Othman, Muhamad Faiz; Yusof, Nor Azah; Abdul Onny, Muhammad Adib; Mat Ail, Noratikah; Abd Rahman, Siti Fatimah (MDPI, 2022)
Designing and implementing various radionuclide production methods guarantees a sustainable supply, which is important for medical use. The use of medical cyclotrons for radiometal production can increase the availability of gallium-68 (68Ga) radiopharmaceuticals. Although generators have greatly influenced the demand for 68Ga radiopharmaceuticals, the use of medical cyclotrons is currently being explored. The resulting 68Ga production is several times higher than obtained from a generator. Moreover, the use of solid targets yields end of purification and end of synthesis (EOS) of up to 194 GBq and 72 GBq, respectively. Furthermore, experiments employing liquid targets have provided promising results, with an EOS of 3 GBq for [68Ga]Ga-PSMA-11. However, some processes can be further optimized, specifically purification, to achieve high 68Ga recovery and apparent molar activity. In the future, 68Ga will probably remain one of the most in-demand radionuclides; however, careful consideration is needed regarding how to reduce the production costs. Thus, this review aimed to discuss the production of 68Ga radiopharmaceuticals using Advanced Cyclotron Systems, Inc. (ACSI, Richmond, BC, Canada) Richmond, Canada and GE Healthcare, Wisconsin, USA cyclotrons, its related factors, and regulatory concerns.